Análisis de la visión en unidades educativas de la provincia de El Oro: caso Santa Rosa, Pasaje y Machala. - Reyes Torres, Jennifer Cecibel (My University, 2019)
The purpose of this degree work was to analyze the business vision of several educational units in the city of Machala, Pasaje, and Santa Rosa through a study of the characteristics and features that determine the degree of similarity between the institutions. The research methodology was a qualitative approach to the analytical inductive method, with explanatory descriptive scope. The research variables are business vision (VI) and organizational culture (DV). The research analyzed elements that limit or facilitate the fulfillment of the vision of each institution based on its organizational culture, in which senior management assumes the commitment to contribute with necessary resources that allow greater coherence between culture and culture. strategy. In the educational units, considering a vision that includes strategic points in the advances of knowledge has been vital to guarantee advances in the ways of approaching, applying and using advantages and innovations in each educational unit. It was known that in all institutions the vision is formulated after developing a socialization with teachers, students, parents and administrative area. They have a vision based on the set of elements that relate to improvements in the physical structure and knowledge of teachers to ensure an education according to what is required by society. It is emphasized that to achieve high prestige in quality of education, everyone's efforts are united to achieve a common goal.
El fin del presente trabajo de titulación fue analizar la visión empresarial de varias unidades educativas de la ciudad de Machala, Pasaje, y Santa Rosa mediante un estudio de las características y rasgos que determinen el grado de similitud entre las instituciones. La metodología de la investigación fue de enfoque cualitativo del método inductivo analítico, con alcance descriptivo explicativo. Las variables de investigación son la visión empresarial (VI) y cultura organizacional (VD). Dentro de la investigación se analizó elementos que limitan o facilitan el cumplimiento de la visión de cada institución basado en su cultura organizacional, en la cual la alta dirección asume el compromiso de contribuir con recursos necesarios que permiten lograr una mayor coherencia entre la cultura y la estrategia. En las unidades educativas plantearse una visión que abarque puntos estratégicos en los avances del conocimiento ha sido vital para garantizar avances en las formas de abordar, aplicar y utilizar ventajas e innovaciones en cada unidad educativa. Se conoció que en todas las instituciones la visión la formulan luego de desarrollar una socialización con profesores, alumnos, padres de familia y área administrativa. Tienen una visión basada en el conjunto de elementos que se relacionan con las mejoras en la estructura física y en conocimientos de los maestros para garantizar una educación acorde a lo exigido por la sociedad. Se destaca que para lograr un alto prestigio en calidad de educación se unen los esfuerzos de todos para conseguir un objetivo en común.
Keywords: VISION; ORGANIZAR; EDUCACIÓN; ESTRATEGIA